Cloning and characterization of feline islet glucokinase - Lindbloom-Hawley, Sara; LeCluyse, Michelle; Vandersande, Vanessa; Lushington, Gerald Henry; Schermerhorn, Thomas (My University, 2014)
Background: Glucokinase (GK) is a metabolic enzyme encoded by the GCK gene and expressed in glucose-sensitive tissues, principally pancreatic islets cell and hepatocytes. The GK protein acts in pancreatic islets as a “glucose sensor” that couples fluctuations in the blood glucose concentration to changes in cellular function and insulin secretion. GCK and GK have proposed importance in the development and progression of diabetes mellitus and are potential therapeutic targets for diabetes treatment. The study was undertaken to determine the nucleotide sequence of feline pancreatic GK cDNA, predict the amino acid sequence and structure of the feline GK protein, and perform comparative bioinformatic analysis of feline cDNA and protein. Routine PCR techniques were used with cDNA from feline pancreas. Clones were assembled to obtain the full length cDNA. Protein prediction and modeling were performed using bioinformatic tools. Results: Full-length feline pancreatic GK cDNA contains a 1398 nucleotide coding sequence with high identity to other pancreatic GK cDNAs. The deduced 465 amino acid feline protein has 15 amino acid substitutions not found in other mammalian GK proteins but maintains high structural homology with human GK. Feline pancreatic GK is highly conserved at nucleotide and protein levels. Residues crucial for substrate binding and catalysis are completely conserved in the feline protein. Conclusion: Molecular analysis predicts that feline pancreatic GK functions similarly to other mammalian GK proteins.
Keywords: Glucose sensor; Pancreas; Carbohydrate metabolism; Hexokinase; Gene expression